Networked theology : negotiating faith in digital culture - Campbell, Heidi, 1970-; Garner, St. (Stephen) (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2016)
This informed theology of communication and media analyzes how we consume new media and technologies and discusses the impact on our social and religious lives. Combining expertise in religion online, theology, and technology, the authors synthesize scholarly work on religion and the internet for a nonspecialist audience. They show that both media studies and theology offer important resources for helping Christians engage in a thoughtful and faith-based critical evaluation of the effect of new media technologies on society, our lives, and the church. - from the publisher.
Introduction: When new media meets faith -- Theology of technology 101: understanding the relationship between theology and technology -- New media theory 101: understanding new media and the network society -- Networked religion: considering how faith is lived in a network society -- Merging the network with theology: who is my neighbor in digital culture? -- Developing a faith-based community reponse to new media -- Engaging appropriately with technology and media.
Includes bibliographical references (pages 149-171) and index.
Keywords: Mass media in religion; Mass media -- Religious aspects -- Christianity; Digital media -- Religious aspects -- Christianity; Digital communications -- Religious aspects -- Christianity; Social media -- Religious aspects -- Christianity; Mass media in religion; Digital Communications -- Religious Aspects -- Christianity; Digital media -- Religious aspects -- Christianity; Mass Media -- Religious Aspects -- Christianity; Social media -- Religious aspects -- Christianity